2018
DOI: 10.3390/ma11050745
|View full text |Cite
|
Sign up to set email alerts
|

Fast Response and Spontaneous Alignment in Liquid Crystals Doped with 12-Hydroxystearic Acid Gelators

Abstract: The spontaneous vertical alignment of liquid crystals (LCs) in gelator (12-hydroxystearic acid)-doped LC cells was studied. Gelator-induced alignment can be used in both positive and negative LC cells. The electro-optical characteristics of the gelator-doped negative LC cell were similar to those of an LC cell that contained a vertically aligned (VA) host. The rise time of the gelator-doped LC cell was two orders of magnitude shorter than that of the VA host LC cell. The experimental results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It has been shown that some organogelators are able to gel thermotropic liquid crystals (LCs), thus forming anisotropic soft solids. The gel structure can enhance anisotropic properties such as electro-optical response in twisted nematic cells or hole mobility . Additionally, it is found that the gel network stabilizes the liquid-crystal (LC) alignment and director patterns. , If the liquid crystalline phase is formed before the gel network structure, the LC can serve as a soft template for the gel, resulting in well-aligned fibers. If the fiber structure is formed first, randomly oriented fibers result in a polydomain LC morphology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some organogelators are able to gel thermotropic liquid crystals (LCs), thus forming anisotropic soft solids. The gel structure can enhance anisotropic properties such as electro-optical response in twisted nematic cells or hole mobility . Additionally, it is found that the gel network stabilizes the liquid-crystal (LC) alignment and director patterns. , If the liquid crystalline phase is formed before the gel network structure, the LC can serve as a soft template for the gel, resulting in well-aligned fibers. If the fiber structure is formed first, randomly oriented fibers result in a polydomain LC morphology.…”
Section: Introductionmentioning
confidence: 99%